2001
DOI: 10.1177/15234220122238526
|View full text |Cite
|
Sign up to set email alerts
|

Structured on-the-Job Training in Developing Nations

Abstract: The problem and the solution. Structured on-the-job training (structured OJT), adapted to a developing nation environment, can significantly improve, at low cost, the performance capability of workers. The chapter presents the rationale for structured OJT in this setting;describes an adapted model to fit the context of a specific developing nation, Cameroun;and presents an application of structured OJT complete with results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…In this article, the authors proposed that the chosen type of OJT matches the type of organization and that matching types, as rules are more effective. Stolovitch and Ngoa-Nguele (2001) reported how S-OJT was adapted in the context of developing West African countries. The results of this study showed that S-OJT is an appropriate approach to the learning context in Cameroon.…”
Section: Performance Quality and Effectiveness Of S-ojtmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, the authors proposed that the chosen type of OJT matches the type of organization and that matching types, as rules are more effective. Stolovitch and Ngoa-Nguele (2001) reported how S-OJT was adapted in the context of developing West African countries. The results of this study showed that S-OJT is an appropriate approach to the learning context in Cameroon.…”
Section: Performance Quality and Effectiveness Of S-ojtmentioning
confidence: 99%
“…These results are similar with issues recognized by Rothwell and Kazanas (1990) related to implementing S-OJT programs in U.S. work settings. Stolovitch and Ngoa-Nguele (2001) designed S-OJT model based on information gathered from observation and analysis of work environment after adaptability to the Cameroon organizational context. Twelve subjects trained at the work site with training materials.…”
Section: Design Implementation and Delivery Of S-ojt Programsmentioning
confidence: 99%
“…OJT as a form of individualized training can be designed and delivered using two basic approaches: structured OJT and unstructured OJT (Jacobs 2003). S-OJT differs from unstructured OJT in that a systematic planning process is used to design and carry out the training (Stolovitch and Ngoa-Nguele 2001), and work behaviors are separated into manageable units and documented in modules (Jones and Jacobs 1997). Unstructured OJT occurs on the worksite but is not logically sequenced.…”
Section: Definition and Features Of S-ojtmentioning
confidence: 99%
“…Outre les limites propres à la formation dans les pays africains [Stolovitch et Ngoa-Nguele, 2001], l'e-formation est l'objet dans le contexte tunisien d'un même décalage entre le discours et la réalité. Il serait alors intéressant de voir quels sont les facteurs qui influencent la mise en oeuvre de l'e-learning parmi les pratiques de formation, en général, et dans les entreprises tunisiennes, en particulier.…”
Section: Introductionunclassified